The Total Cost to the Health Care System in Medicare and Medicaid Patients for the Treatment of Cervical Myelopathy. Issue 1 (February 2019) - Schroeder, Gregory D.; McKenzie, James C.; Casper, David S.; Kurd, Mark F.; Hilibrand, Alan S.; Woods, Barret I.; Radcliff, Kris E.; Rihn, Jeffery A.; Anderson, David Greg; Vaccaro, Alexander R.; Kepler, Christopher
Abstract : Introduction: Cervical myelopathy is a common indication for spine surgery. Modern medicine demands high quality, cost-effective treatment. Most cost analyses fail to account for complication costs from nonoperative treatment. The purpose is to compare the total health care costs for operative versus nonoperative treatment of cervical myelopathy. Methods: The Center for Medicare and Medicaid Services Carrier File from 2005 to 2012 was reviewed using the PearlDiver database, representing a 5% sampling of Medicare billings which diagnosed patients with cervical myelopathy by International Classification of Diseases 9 code. Patients were separated into operative and nonoperative cohorts, and the total health care expenditures per patient normalized to 2012 dollars were collected. Results: A total of 3209 patients were included, and 1755 (55.87%) underwent surgery. A 6-year cost analysis performed on 309 patients over the age of 65 from 2006 undergoing surgery resulted in a nonsignificant increase in total health care expenditures (166, 192 vs. 153, 556; P =0.45). Operative treatment had a net decrease in total health care costs following the first year of surgery. Conclusions: There is no significant difference in the total health care expenditures for operative versus nonoperative treatment of cervical myelopathy after 3 years. It is critical to understand that nonoperative treatment of this progressive disease leads to a substantial increase in total health care expenditures with increased risk of falls, injury, and further morbidity.